(untitled) (Research, Society and Development, 2020)
The presence of biofilms on food processing surfaces is a constant concern and can cause economic damage and impacts on public health. The aim of this work was to evaluate the development of P. fluorescens on the stainless steel surface, to analyze the CIP (clean in place) hygiene considering different geometries, to investigate the flow fluid dynamics and to determine the consumption of the inputs in this process. A circulation line with the characteristics of a dairy was used. The surface sampling was done using the swab technique and the performance of the process was evaluated based on decimal reductions considering the initial population adhered. The fluid dynamics study was carried out with FLUENT software and the consumption was determined by means of flow and electric current sensors. The results showed that P. fluorescens adhered to the surface reaching an average of 4.31 ± 0.26 log CFU∙cm-2, with the production of exopolysaccharides during usual time of industry operation. The decimal reduction was not significantly different among the pipe geometries in straight section, elbow, expansion and reduction. The stretch with branching in tee was statistically different from the others due to a zone of stagnation and fluid recirculation. The rinses were the stages that consumed the most water and the alkaline cleaning demanded more energy to execute the CIP. The geometries showed microbiological safety after CIP process, except tee. In addition, the expressive demand for water and energy for the execution of the process was evident.